Alveolar ridge preservation in post-extraction sockets using concentrated growth factors: a split-mouth, randomized, controlled clinical trial - Elayah, Sadam Ahmed; Younis, Hamza; Cui, Hao; Liang, Xiang; Sakran, Karim Ahmed; Alkadasi, Baleegh; Al-Moraissi, Essam Ahmed; Albadani, Mohammed; Al-Okad, Wafa; Tu, Junbo; Na, Sijia (Frontiers in Endocrinology, 2023)
Aim The aim of this clinical trial was to assess the impact of autologous concentrated growth factor (CGF) as a socket-filling material and its ridge preservation properties following the lower third molar extraction. Materials and methods A total of 60 sides of 30 participants who had completely symmetrical bilateral impacted lower third molars were enrolled. The primary outcome variables of the study were bone height and width, bone density, and socket surface area in the coronal section. Cone beam computed tomography images were obtained immediately after surgery and three months after surgery as a temporal measure. Follow-up data were compared to the baseline using paired and unpaired t-tests. Results CGF sites had higher values in height and width when compared to control sites (Buccal wall 32.9 ± 3.5 vs 29.4 ± 4.3 mm, Lingual wall 25.4 ± 3.5 vs 23.1 ± 4 mm, and Alveolar bone width 21.07 ± 1.55vs19.53 ± 1.90 mm, respectively). Bone density showed significantly higher values in CGF sites than in control sites (Coronal half 200 ± 127.3 vs -84.1 ± 121.3 and Apical half 406.5 ± 103 vs 64.2 ± 158.6, respectively). There was a significant difference between both sites in the reduction of the periodontal pockets. Conclusion CGF application following surgical extraction provides an easy, low-cost, and efficient option for alveolar ridge preservation. Thus, the use of CGF by dentists during dental extractions may be encouraged, particularly when alveolar ridge preservation is required. Clinical trial registration TCTR identification, TCTR20221028003.